Transition. the magazine of Africa and the diaspora. (Indiana University Press, 2015)
December 2014 marked a year since the passing of Nelson Mandela-a man who was as much myth as flesh and blood. Transition pays tribute to Mandela's worldly attainments and to his otherworldly sainthood. Featuring remembrances from Wole Soyinka, Xolela Mangcu, Pierre de Vos, and Adam Habib, this issue assembles Mandela's staunchest allies-for whom he approached saintliness-as well as his most entrenched critics. Other contributors consider the iconicity of Mandela-including his representations in films; the importance of boxing to his political career; his time studying with the revolutionary a.